Community Service Regarding the Processing of Various Produced Afkir Bali Female Ducks in Tihingan Village, Banjarangkan District, Klungkung District - Rukmini, Ni Ketut Sri; Yudiastari, Ni Made; Suwitari, Ni Ketut Etty; Semadi, I Wayan Adrika; Putra, I Ketut Prabawa (Asian Journal of Community Services, 2024)
Based on the results of a survey at the partner location, it was discovered that the partner had no knowledge of making processed salted eggs and cull duck meat. Therefore, the community service team provided training and assistance in making salted eggs and processed cull duck meat as well as procuring equipment to support training activities. Training on processing cull duck meat and duck eggs has gone smoothly. Breeders have been able to produce salted eggs and meat from ungkep ducks and betutu ducks. From the activities, an increase in the economic value of duck eggs into salted eggs has been achieved by 36% and an increase in the economic value of cull duck meat by 30%. Farmers were very enthusiastic about participating in the activity because they gained new knowledge and skills in processing duck eggs and duck meat.